Entre comida, artesanato e… fuleragem? Uma etnografia na feira de artesanato e artes da Praça dos Namorados - Domingues, Fabiana Florio (2016)
This study had its goal set on understanding the symbolic aspects related to the craft and art fair space at Praça dos Namorados, through the perspectives of passers-by and exhibitors sharing the site. Therefore, the author develop interpretations about